Acute epiploic appendagitis – a rare differential diagnosis of acute abdomen - Harling, Lisa; Peglow, Steffi; Eger, Kai; March, Christine; Croner, Roland. S.; Meyer, Frank (Zeitschrift für Gastroenterologie, 2022)
Background Acute epiploic appendagitis is a rare differential diagnosis of unclear or acute abdomen.Aim To describe – by means of a scientific case report – the extraordinary diagnosis of acute epiploic appendagitis along with contained diverticulitis and incarcerated herniation of the greater omentum into the hernial sac of a former trocar site (medical history, significant for laparoscopic ovarian cyst removal) in a 29-year-old female based on experiences obtained in the successful clinical case management, and on selective references from medical scientific literature.Case summary Medical history: A 29-year-old female was admitted with abdominal pain in the lower left quadrant. She reported a laparoscopic ovarian cyst removal 3 years prior.Physical examination of the abdomen revealed tenderness in the lower left quadrant without a palpable mass.Leading diagnoses were found using transabdominal ultrasound and confirmed by an abdominal CT scan; namely, incarcerated trocar hernia, diverticulitis of sigmoid colon, and acute epiploic appendagitis.Therapeutic approach was comprised of an explorative laparoscopy (because of the incarcerated hernia), adhesiolysis, removal of a tip of the greater omentum out of the hernial sac, closure of the hernial orifice, and removal of an unclear, inflamed, and bloody fatty tissue from the wall of the descending colon (histopathological investigation confirmed acute epiploic appendagitis). This was flanked by conservative treatment of diverticulitis of the sigmoid colon.Further clinical course was uneventful, with discharge on the 3rd postoperative day with favorable long-term outcome, characterized by no further complaints for 15 months.Discussion Acute epiploic appendagitis is an inflammatory, usually self-limiting condition of the epiploic appendages of the colon. It typically manifests with abdominal pain in the lower left quadrant. Imaging is an important diagnostic tool to determine whether the patient has, in fact, acute epiploic appendagitis, so recognizing the characteristic oval lesions with the surrounding inflammation and central fat attenuation on CT, as well as the hyperechoic oval lesions with a hypoechoic peripheral band on ultrasound images is crucial. Nevertheless, it is often overlooked in patients and confused with other differential diagnoses, such as appendicitis or diverticulitis. Although the condition appears infrequently, it is essential to be proficient in the diagnostic evaluation, as a misdiagnosis may lead to unnecessary treatment and even surgical intervention.In conclusion, the patient was initially diagnosed with an incarcerated abdominal hernia, and therefore subsequently underwent surgery. The inflamed epiploic appendage was discovered in laparoscopic exploration, removed, and confirmed through the histopathology report. This is an approach to be performed with great caution so as not to 1. misinterpret an inflamed diverticula or covered perforation of it as well as not 2. overlooking a peritoneal tumor lesion.
Keywords: Akute Appendagitis epiploica; unklares/akutes Abdomen; Differenzialdiagnose; Diverticulitis; peritoneale Tumorläsion